Strategic Human Capital Development in Islamic Microfinance: A Qualitative Study of Competitive Advantage - Wandy Zulkarnaen (International Journal of Nusantara Islam, 2026)
The Islamic banking industry in Indonesia is growing rapidly, especially after the enactment of regulations such as Law No. 21 of 2008 concerning Islamic Banking. However, Islamic People's Banks (BPRS) face challenges in managing Human Resources (HR), including limited training, a shortage of workers with an Islamic economic background, and challenges in adapting to digitalization. A strategy for developing HR based on Islamic values is crucial to enhancing BPRS's competitiveness in West Java. This study uses a qualitative, descriptive approach. Data were collected through in-depth interviews, direct observation, and document analysis related to HR policies in BPRS West Java. The analysis was carried out through a process of reduction, presentation, and drawing conclusions to obtain systematic findings. The results of this study indicate that HR management is related to the maqasid of sharia, especially in the aspects of hifz al-mal, hifz ad-din, and hifz al-aql, although its implementation still faces regulatory and business challenges. The implemented HR strategy model includes Islamic value-based recruitment, continuous training, performance evaluation based on sharia principles, and HR digitalization, but regulatory alignment and technology adoption remain obstacles.